Rethinking evidence: a multidisciplinary approach to the use of synthetic data in healthcare - part I (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
This essay explores the role of synthetic data in clinical trials and Health Technology Assessment, highlighting its transformative potential on epistemological and legal levels. Adopting a multidisciplinary approach, it examines the compatibility of such data with European health law and the evidence-based design paradigm. The aim is to propose a systemic interpretation of the current legal framework that legitimizes synthesization as an emerging form of evidence generation, calling for the development of a new legal grammar capable of reconciling technological innovation, fundamental rights, and the sustainability of healthcare systems.
Keywords: Synthetic data; clinical trials; Health Technology Assessment (HTA); artificial intelligence; data protection